Current patient and healthcare worker attitudes to eHealth and the personally controlled electronic health record in major hospitals. Issue 6 (3rd June 2016) - Armani, R.; Mitchell, L. E.; Allen‐Graham, J.; Heriot, N. R.; Kotsimbos, T.; Wilson, J. W.
Abstract : Background: The current health system in Australia is comprised of both electronic‐ and paper‐based medical records. The Federal Government has approved funding for the development of an individual health identifier and a universally adopted online health repository. Aims: To determine attitudes and beliefs of patients and healthcare workers regarding the use of stored medical information and the personally controlled electronic health record (PCEHR) in selected major hospitals in Victoria. Methods: Qualitative survey of patients and healthcare workers ( n = 600 each group) conducted during 2014 across five major hospitals in Melbourne to measure the awareness, attitudes and barriers to electronic health and the PCEHR. Results: Of the patients, 93.3% support the concept of a shared electronic healthcare record, 33.7% were aware of the PCEHR and only 11% had registered. The majority of healthcare workers believed that the presence of a shared health record would result in an increased appropriateness of care and patient safety by reducing adverse drug events and improving the timeliness of care provided. However, only 46% of healthcare workers were aware of the PCEHR. Conclusions: This study provides a baseline evaluation of perceptions surrounding eHealth and PCHER in acute health services in five metropolitan centres. While there appears to be a readiness for adoption of these strategies for healthcare documentation, patients require motivation to register for the PCEHR, and healthcare workers require more information on the potential benefits to them to achieve more timely and efficient care.